Analysis of face stability for shallow shield tunnels in sand - Qiang, Sihan; Zhao, Lizhi; Wang, Xuehai; Li, Xiaoming; Wang, Fengnian (Frontiers in Earth Science, 2023)
Numerical simulation and theoretical analysis are combined to study the face stability of shallow shield tunnel in sand. Firstly, Numerical simulation is employed to study the collapse of tunnel face, the limit support pressure and collapse zone shape are obtained. The new failure model suitable for shallow tunnel is constructed based on numerical simulations. Analytic solution of limit support pressure is derived based in the limit analysis upper bound theory. The accuracy and applicability of the proposed model are verified by comparing with numerical results and classical analytical models. In addition, the proposed model provides a more accurate description of the phenomenon where soil arches can't be formed for shallow tunnels in sand, leading to a higher accuracy in calculating the limit support pressure. Finally, using the proposed model, the influence of various factors on stability of tunnel face is analyzed, and the mechanism of collapse of tunnel face is revealed.